EVA as an indicator of financial performance in Tech companies during the Covid-19 pandemic - Kumalasari, Riesta Devi; Herdina, Ajeng Mira; Murniati, Murniati; Purnama, Priska Arindya; Prasetyo, Yogi Tri (Manajemen dan Bisnis, 2023)
During the Covid-19 pandemic, many technology companies recorded sales volume increases. It happened because the pandemic pushed everyone to utilise technology devices for daily activities. Therefore, it drives the sales of technology companies to improve. This research uses the EVA (Economic Value Added) indicator as a financial analysis tool to evaluate the financial performance of companies in the technology sector on the Indonesia Stock Exchange before and during the Covid-19 pandemic. This research uses technology companies' financial statements from January 2019 - December 2020 as secondary data. The research analysis is in the form of a descriptive analysis of EVA calculation. The findings revealed that two of the four selected technology companies have a positive EVA value, which indicates that the two companies have been able to provide added value from their operational activities even before the Covid-19 pandemic occurred in Indonesia. Meanwhile, another company generate a negative EVA, which suggests that the company's management has not been able to create added value for the company. The company's ability to maintain financial sustainability represented by EVA value is ultimately not only defined by certain situations, such as a pandemic, but also by its ability to formulate a capital structure strategy.